2000
DOI: 10.3354/meps194263
|View full text |Cite
|
Sign up to set email alerts
|

The influence of size on striped bass foraging

Abstract: Striped bass Morone saxahhs is an abundant piscivorous fish in estuaries and coastal systems along the US Atlantic coast and has also been stocked into systems in Cahfornia and the continental US. Despite the widespread distnbution of striped bass and their relative importance as a predator in these systems, little is known about how relative size of prey affects their prey capture success. This study measured the capture success and handling times of striped bass fed live shiners Notropis athennoides and N. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…3). The relative predator length is frequently used when describing predator and prey relations in size-structured populations (e.g., Scharf et al 1998, Hartman 2000. Our data suggest it is legitimate to assume that the parameters are independent on predator size if corrected for prey size for the size combinations used in our experiments.…”
Section: Model Descriptionmentioning
confidence: 78%
“…3). The relative predator length is frequently used when describing predator and prey relations in size-structured populations (e.g., Scharf et al 1998, Hartman 2000. Our data suggest it is legitimate to assume that the parameters are independent on predator size if corrected for prey size for the size combinations used in our experiments.…”
Section: Model Descriptionmentioning
confidence: 78%
“…Popova 1978, Gleason & Bengtson 1996, Scharf et al 1997, Buckel et al 1998, Manderson et al 1999, 2000, Hartman 2000, it is often small rather than large piscivores that preferentially target small prey fish (Rice et al 1993). Additionally, a number of studies have shown that piscivores are able to consume prey that are large relative to the predator's size (Table 2).…”
Section: What Constitutes 'Shallow Water'?mentioning
confidence: 99%
“…This is possible because many benthic predators such as crabs, naticid and muricid gastropods, and fishes are generalist feeders, consuming those prey items that yield within a certain time (e.g. Fairweather & Underwood 1983, Brown & Haight 1992, Hartman 2000, Bishop et al 2008. Among armoured species, processes that weaken shell thickness or strength may confer greater vulnerability to predation (e.g.…”
Section: Introductionmentioning
confidence: 99%